Clinical outcomes of nephrocalcinosis in preschool-age children: association between nephrocalcinosis improvement and long-term kidney function - Woo, Hyun Ah; Lee, Hyeonju; Choi, Young Hun; Min, Jeesu; Kang, Hee Gyung; Ahn, Yo Han; Lee, Hyun Kyung (Frontiers in Pediatrics, 2023)
We evaluated the long-term clinical outcomes of nephrocalcinosis (NC) according to etiology and grade in preschool-age children with NC.We retrospectively analyzed the clinical outcomes and disease grade of children with NC classified into three groups according to etiology: prematurity, tubular disorders, and others. Overall, 67 children were diagnosed with NC (median age, 0.76 years; interquartile range (IQR) 0.46-2.14 years). The etiologies of NC included prematurity (28.4%), tubular disorders (25.4%), and others (46.3%).Moreover, 56 (83.6%) children were asymptomatic and diagnosed accidentally through kidney ultrasonography. Newly diagnosed underlying diseases were greater in the tubular disorders group than in the other two groups (P = 0.001). Significantly more newly diagnosed NCs were grade 3 than grade 1 (P = 0.003). The median estimated glomerular filtration rate (eGFR) changed from 96.1 (IQR 68.8-119.2) mL/min/1.72 m 2 at diagnosis to 90.9 (IQR 76.4-106.4) mL/min/1.72 m 2 at the last follow-up, without a significant difference (P = 0.096). Changes in the kidney function did not differ according to etiology. However, patients without improvement in NC grade showed a decrease in eGFR from 98.1 (IQR 71.1-132.9) to 87.4 (IQR 74.0-104.1) mL/min/1.73 m 2 (P = 0.023), while patients with improved NC grade did not show any change in the kidney function. Early recognition, especially in NC grade 3, can help uncover further diagnoses, such as tubular disorders. Long-term kidney function depends on whether the NC grade improves.